PERILAKU KONSUMEN TERHADAP PEMBELIAN BUAH-BUAHAN PADA SAAT PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT DARURAT DI KOTA PONTIANAK - Rindang, Kurnianto; Dolorosa, Eva; Maswadi, Maswadi (Agros Journal of Agriculture Science, 2024)
Consumer behavior is behavior exhibited by people in terms of planning, buying and using economic goods and services. Fruit is a horticultural product that has bright prospects so that it can be developed as a source of economic growth in the agricultural sector.  The CoronaVIrus Disease 2019 (Covid-19) pandemic has changed many things such as cleanliness, health and changing human consumption patterns. Since the Covid-19 pandemic entered Indonesia, the fruits consumption campaign has continued to be intensified. Pontianak City is a city that enforces Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM). Seeing this situation, it is necessary to further investigate how consumer behavior towards purchasing fruits during emergency PPKM. The data in this study was secondary data with 133 respondents netted by purposive sampling method. The variables in this study are Cultural, Social, Personal and Psychological. Based on the results of research using factor analysis, it can be concluded that the factors that influence consumer behavior towards purchasing fruits during PPKM in Pontianak City consist of 3 factors, namely Social, Personal, and Psychological. There is 1 factor that is less influential, namely the Cultural factor. The most dominant factor is the psychological factor with indicators included Motivation, Perception, and Belief and Stance.